2019
DOI: 10.1038/s41598-019-46170-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-214 targets PTK6 to inhibit tumorigenic potential and increase drug sensitivity of prostate cancer cells

Abstract: Prostate cancer is the most commonly diagnosed cancer in men with African American men disproportionally suffering from the burden of this disease. Biomarkers that could discriminate indolent from aggressive and drug resistance disease are lacking. MicroRNAs are small non-coding RNAs that affect numerous physiological and pathological processes, including cancer development and have been suggested as biomarkers and therapeutic targets. In the present study, we investigated the role of miR-214 on prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 64 publications
2
33
0
Order By: Relevance
“…Migration assay. The effect of miR-205-5p overexpression on the migratory ability of skin cancer cells was analyzed by a wound healing migration assay as described previously 17 . Cells were transfected with miR-205-5p or NC mimic and transfected cells were plated, and the cell monolayer was scraped using a micropipette tip (A 0 ).…”
Section: Immunohistochemical Analysis (Ihcmentioning
confidence: 99%
See 1 more Smart Citation
“…Migration assay. The effect of miR-205-5p overexpression on the migratory ability of skin cancer cells was analyzed by a wound healing migration assay as described previously 17 . Cells were transfected with miR-205-5p or NC mimic and transfected cells were plated, and the cell monolayer was scraped using a micropipette tip (A 0 ).…”
Section: Immunohistochemical Analysis (Ihcmentioning
confidence: 99%
“…miRNAs are small singlestranded non-coding RNAs that modulate post-transcriptional gene expression by binding to the 3′ untranslated regions (3′UTRs) of target mRNAs. The binding of miRNAs to 3′UTRs of target mRNA regulates both the stability and translation of mRNA transcripts and thus affects gene expression 17 . Reports suggest that by directly targeting key gene expression, miRNAs modulate various cellular processes such as cell proliferation/survival, cell-cycle control, cell apoptosis, the stress response, cell metabolism, development, and differentiation 18,19 .…”
mentioning
confidence: 99%
“…It is conventionally used for the treatment of liquid malignancies such as mantle cell lymphoma and chronic lymphocytic leukemia. The results demonstrated that inhibiting PTK6 using miR-214 alone or in concomitant administration of miR-214 and IBT reduced cell proliferation and viability in PCa [154]. Zangoue…”
Section: Non-receptor Tyrosine Kinasesmentioning
confidence: 95%
“…While there was no v-miRNA with the same 6mer seed as miR-34a-5p, we found a v-miRNA that shared the same 2-7 nucleotides present in the predominant 5p arm of the miR-15/16-5p miRNA family. kshv-miR-K12-6-5p (miR-K12-6-5p) contains a GC-rich trinucleotide repeat seed sequence that is found in three miRNA families with ample published evidence for having tumor suppressive activities: miR-15/16-5p (Bonci et al, 2008;Calin et al, 2008;Calin et al, 2002;Han et al, 2017;Hu et al, 2018;Huang et al, 2015;Ke et al, 2013;Klein et al, 2010;Lovat et al, 2015;Lovat et al, 2018;Maximov et al, 2019;Pekarsky and Croce, 2015;Rahman et al, 2014;Yang et al, 2014), miR-214-3p (Cagle et al, 2019;Fan et al, 2017;Huang et al, 2014;Liu et al, 2016;Long et al, 2015;Pang et al, 2018;Phatak et al, 2016;Wang et al, 2012;Yang et al, 2015;Yang et al, 2018b;Zhang et al, 2017), and miR-103/107-3p Feng et al, 2012;Fu et al, 2019;Gao et al, 2017;Piao et al, 2012;Sharma et al, 2017;Song et al, 2015;Yamakuchi et al, 2010;Yang et al, 2018a;Zhang et al, 2019) (Figure 2A). miR-K12-6-5p shares an 8mer seed sequence with miR-15a-5p, miR-15b-5p, and miR-16-5p, and a 6, 7 or 8mer seed with other members of this family (Figure 2A).…”
Section: The Mir-15a/b-5p/16-5p Family Kills Cells In Part Through 6mmentioning
confidence: 99%